Reph, a Regulator of Eph Receptor Expression in the Drosophila melanogaster Optic Lobe - Dearborn, Richard E. (Public Library of Science, 2012)
Receptors of the Eph family of tyrosine kinases and their Ephrin ligands are involved in developmental processes as diverse as angiogenesis, axon guidance and cell migration. However, our understanding of the Eph signaling pathway is incomplete, and could benefit from an analysis by genetic methods. To this end, we performed a genetic modifier screen for mutations that affect Eph signaling in Drosophila melanogaster. Several dozen loci were identified on the basis of their suppression or enhancement of an eye defect induced by the ectopic expression of Ephrin during development; many of these mutant loci were found to disrupt visual system development. One modifier locus, reph (regulator of eph expression), was characterized in molecular detail and found to encode a putative nuclear protein that interacts genetically with Eph signaling pathway mutations. Reph is an autonomous regulator of Eph receptor expression, required for the graded expression of Eph protein and the establishment of an optic lobe axonal topographic map. These results reveal a novel component of the regulatory pathway controlling expression of eph and identify reph as a novel factor in the developing visual system.